PERAN HUKUM DALAM KEBIJAKAN PERLINDUNGAN TERUMBUH KARANG - Aimar Rendra P.A; Dwi Juniartho (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Indonesia has a sizeable maritime area and rich biodiversity. Nonetheless, there are a number of dangers to Indonesia's maritime ecosystem, including pollution, overfishing, damage to coral thermam, and climate change. When it comes to safeguarding the maritime environment, law is very important. Laws can be used to create regulations that enforce the rule of law, safeguard the maritime environment, and punish violators. Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands, and Government Regulation Number 62 of 2012 concerning Protection and Management of the Marine Environment are just some of the policies that have been issued by the Indonesian government to protect the marine environment